Overcoming the Inadequacy of Economic Dynamics Models - Vasylenko, Yuriy (Ekonomika, 2022)
Known models of economic dynamics are too aggregate, so inadequate to the real economy. The analyst will not be able to identify the real dynamics of the economy among the big mistakes. They have no connection between investments, their efficiency, and the rate of economic growth. There is no transition from the optimal share of savings in the country to the agents’ optimal shares, managing investment sources.To link investment and the pace of economic growth, the author introduced the concept of technical productivity of investments, which measures their ability to change the rate of material or labor costs.Based on the technical productivity of investment, the author has derived the equation (not identity) of economic dynamics.Instead of the highly aggregated models, the author developed an adequate causal simulation model, reflecting the economy as a closed system with positive feedback of the investment from incomes and economic growth from investment. The author determined the dynamics of the Ukrainian economy with different technical productivity of investment on this model.
Keywords: inadequacy of high aggregated models of economic dynamics; technical productivity of investments; causal simulation model of economic dynamics; shadow economy; forecast